2019
DOI: 10.1038/s41598-019-52626-3
|View full text |Cite
|
Sign up to set email alerts
|

The citrus flavonoid naringenin impairs the in vitro infection of human cells by Zika virus

Abstract: The Zika virus (ZIKV) is an arthropod-borne virus that belongs to the Flaviviridae family. The ZIKV infection is usually asymptomatic or is associated with mild clinical manifestations; however, increased numbers of cases of microcephaly and birth defects have been recently reported. To date, neither a vaccine nor an antiviral treatment has become available to control ZIKV replication. Among the natural compounds recognized for their medical properties, flavonoids, which can be found in fruits and vegetables, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
68
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(70 citation statements)
references
References 74 publications
2
68
0
Order By: Relevance
“…Interestingly, in the same study (Nahmias et al, 2008), Nar was shown to be effective to reduce Hepatitis C virus secretion by 80% when added at 200 µM in infected Huh7.5.1 human hepatoma cell line. Moreover, that Nar treatment could be a promising strategy to inhibit virus replication and infection is further confirmed by interesting studies on the influenza A virus, dengue virus and Zika virus (Dong et al, 2015;Frabasile et al, 2017;Cataneo et al, 2019). Antiviral effect of some flavonoids and Nar through blocking viral proteases activity in different experimental models has been also reported (de Sousa et al, 2015;Lulu et al, 2016;Lim et al, 2017;Jo et al, 2020).…”
mentioning
confidence: 77%
“…Interestingly, in the same study (Nahmias et al, 2008), Nar was shown to be effective to reduce Hepatitis C virus secretion by 80% when added at 200 µM in infected Huh7.5.1 human hepatoma cell line. Moreover, that Nar treatment could be a promising strategy to inhibit virus replication and infection is further confirmed by interesting studies on the influenza A virus, dengue virus and Zika virus (Dong et al, 2015;Frabasile et al, 2017;Cataneo et al, 2019). Antiviral effect of some flavonoids and Nar through blocking viral proteases activity in different experimental models has been also reported (de Sousa et al, 2015;Lulu et al, 2016;Lim et al, 2017;Jo et al, 2020).…”
mentioning
confidence: 77%
“…They are key mediators of various biological processes in plants, such as nitrogen fixation, photosynthesis, energy transfer, and anti-oxidation [ 15 ]. Moreover, their activities extended towards anti-cancer, antivirals [ 10 , 12 , 17 ], and anti-inflammation [ 29 , 30 ]. Generally, flavanones are further metabolized to flavones by the addition of a double bond to C2–C3 of ring C, thus decreasing the aqueous solubility ( Supplementary Figure S6 ) [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…To overcome the challenge, a flavanone substrate with higher solubility was considered as a replacement. Moreover, pinocembrin (5,7-dihydroxyflavanone), was previously reported as a potential inhibitor of dengue [ 10 , 11 ] and Zika viruses [ 12 ] with possible targets at viral NS2B-3 protease [ 12 , 13 , 14 ]. Moreover, anti-flaviviral inhibition was also reported in other flavanones, such as pinostrobin, naringenin, hesperitin, and their derivatives.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that naringenin suppressed respiratory overexpression and eosinophilic airway inflammation in asthma and thus, reduced acute neutrophilic airway inflammation by blocking the NF-κB pathway [ 106 ]. Naringenin has been found to impair replication of several viruses in human cells such as dengue, Zika and Chikungunya viruses [ 107 109 ] and to guarantee a significant protection against LPS-induced acute lung injuries through its anti-inflammatory, antioxidant, antinitrosative and antiapoptotic effects [ 110 , 111 ]. Due to its strong anti-inflammatory and anti-oxidant effects, narigenin may be utilized against pneumonia companied with the spread of COVID-19.…”
Section: Naringeninmentioning
confidence: 99%